2005
DOI: 10.1186/bcr1005
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptors participation in angiogenic response induced by macrophages from mammary adenocarcinoma-bearing mice

Abstract: Introduction The role of macrophages in tumor progression has generated contradictory evidence. We had previously demonstrated the ability of peritoneal macrophages from LMM3 murine mammary adenocarcinoma-bearing mice (TMps) to increase the angiogenicity of LMM3 tumor cells, mainly through polyamine synthesis. Here we investigate the ability of the parasympathetic nervous system to modulate angiogenesis induced by TMps through the activation of the muscarinic acetylcholine receptor (mAchR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Particularly M 1 and M 2 receptors participate in the angiogenic response exerted by CARB modulating arginine metabolism via arginase II. These results are coincident with previous reports published by our laboratory that demonstrated M 1 and M 2 collaborative actions on urea production by arginase II in the angiogenic pro-tumor effects exerted by macrophages purified from LMM3 tumor bearers (de la Torre et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…Particularly M 1 and M 2 receptors participate in the angiogenic response exerted by CARB modulating arginine metabolism via arginase II. These results are coincident with previous reports published by our laboratory that demonstrated M 1 and M 2 collaborative actions on urea production by arginase II in the angiogenic pro-tumor effects exerted by macrophages purified from LMM3 tumor bearers (de la Torre et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…Muscarinic receptors are expressed on immune cells, including macrophages (15,31,32), which produce TNF during endotoxemia (33,34). Vagal efferents, distributed throughout the reticuloendothelial system and other peripheral organs are positioned to rapidly transmit the antiinflammatory signal to these cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Mps could participate in this process, but little is known about the mechanisms involved in it (Nucera et al, 2011). We had previously reported that peritoneal Mps from tumor‐bearing mice are able to induce a strong neovascular response in the skin of singeneic mice (de la Torre et al, 2005). Similar results accompanied by the increment of VEGF‐A and MMP‐9 are observed when LPS‐treated Mps are inoculated in the skin of singeneic mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%